2019
DOI: 10.5222/mmj.2019.39197
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Bronchitis in a 4 Year-Old Boy Presenting with a Foreign Body Aspiration: A Rare Entity

Abstract: Plastic bronchitis is a rare disease of pediatric age resulting from the fibrinous mucus plugs obstructing the airway. Plastic bronchitis can be secondary to many pulmonary and systemic diseases; but also it can be idiopathic. It is an important entity because it can present with acute respiratory system failure symptoms like non-productive cough, dyspnea and wheezing mimicking foreign body aspiration. Here, we present a 4-year-old boy diagnosed as plastic bronchitis by bronchoscopy. A 4-year-old boy was broug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…PB should be considered in patients with atelectasis on chest X-rays. [15][16][17] Girit et al 15 reported a 4-year-old male patient who presented with a cough. Atelectasis was detected in the right upper pulmonary lobe, and he underwent bronchoscopy with the prediagnosis of foreign body aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PB should be considered in patients with atelectasis on chest X-rays. [15][16][17] Girit et al 15 reported a 4-year-old male patient who presented with a cough. Atelectasis was detected in the right upper pulmonary lobe, and he underwent bronchoscopy with the prediagnosis of foreign body aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis was PB, and he was treated with flexible bronchoscopy. 15 However, atelectasis can be associated with pediatric asthma in as many as 1.62% of cases and is usually localized to the medial segment of the middle lobe and the lingula. 18 In our PB case series, atelectasis, and asthma were among the most common presenting and underlying conditions, diffuse obstruction of the central airways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations